Hydrochlorothiazide increases risk of nonmelanoma skin cancer in an elderly Japanese cohort with hypertension: The Shizuoka studyCapsule Summary - Hideo Hashizume, MD, PhD; Eiji Nakatani, PhD; Hatoko Sasaki, DrPH; Yoshiki Miyachi, MD, PhD (Elsevier, 2023)
Background: Hydrochlorothiazide (HCT), a widely used hypertensive drug, has photocarcinogenic potential, leading to concerns about the development of nonmelanoma skin cancers (SCs) after intake. Despite substantial numbers of observational studies, the results remain inconsistent especially among Asian countries. Objective: To assess the incidence of nonmelanoma SCs in hypertensive Japanese HCT users compared with nonusers. Methods: A population-based, cohort nested, propensity score-matched study was conducted using the Shizuoka Kokuho database. All participants were patients aged ≥60 years. Hazard ratios for SC incidence were calculated in the matched cohorts using the propensity scores of potential confounders, sex, age category, comorbidities, and administration of methotrexate, cyclosporin, and statins. Results: The risk of SC was higher in HCT users than in nonusers (hazard ratio, 1.58; 95% confidence interval, 1.04-2.40), with preferential sun-exposed location and a tendency to develop squamous cell carcinoma, but not basal cell carcinoma or Bowen disease. Limitations: No additional information was available from other than medical records. The data were confined to a Japanese population. Conclusion: HCT use increases the risk of SC in Japanese patients with hypertension and a dark skin type, highlighting the increased risk of SC among HCT users in the aging society worldwide.